Osteoarticular complications of brucellosis: The diagnostic value and importance of detection matrix metalloproteinases - Maida Šiširak; Mirsada Hukić (Acta Medica Academica, 2015)
Objectives. Matrix metalloproteinases (MMPs) has been implicated in the pathogenesis of infective, cancer and autoimmune diseases. In this study, we investigated the serum level of MMPs and its clinical importance in human brucellosis. Patients and methods. This study included 60 brucellosis patients treated at the Clinic for Infectious Diseases, Clinical Centre, University of Sarajevo. Matrix metalloproteinases serum levels were quantified by ELISA. Results. The investigation involved three groups: 30 patients with complications, 30 patients without complications of brucellosis and 30 healthy control examinees. The complications of human brucellosis varied but osteoarticular involvement dominated (n=21/30; 70%). Matrix metalloproteinases serum levels in the patients with complications were highest. The serum level of MMP-1 in patients with complications was the highest at 9.45; in patients without complications it was 3.78 and in the control examinees it was lowest at 3.62 (p=0.001). The serum level of MMP-9 in patients with complications was the highest at 105.66; in patients without complications 64.67, and in the control examinees it was lowest at 37.32 (p=0.001). The serum level of MMP-13 in patients with complications was highest at 138.86; in patients without complications at 64.85; and in the control examinees it was the lowest at 29.55 (p=0.001). Pearson’s coefficient showed a statistically significant positive correlation between levels of tested matrix metalloproteinases and development complications in human brucellosis (p=0.001). Conclusion. This study showed the diagnostic value and importance of detection of matrix metalloproteinases in human brucellosis. MMPs are a useful serum biomarker for assessment of disease activity.